Enhanced Immune Response in Immunodeficient Mice Improves Peripheral Nerve Regeneration Following Axotomy - Bombeiro, André L.; Santini, Júlio C.; Thomé, Rodolfo; Ferreira, Elisângela R. L.; Nunes, Sérgio L. O.; Moreira, Bárbara M.; Bonet, Ivan J. M.; Sartori, Cesar R.; Verinaud, Liana; Oliveira, Alexandre L. R. (Frontiers in Cellular Neuroscience, 2016)
Injuries to peripheral nerves cause loss of motor and sensory function, greatly affecting life quality. Successful repair of the lesioned nerve requires efficient cell debris removal, followed by axon regeneration and reinnervation of target organs. Such process is orchestrated by several cellular and molecular events in which glial and immune cells actively participate. It is known that tissue clearance is largely improved by macrophages, which activation is potentiated by cells and molecules of the acquired immune system, such as T helper lymphocytes and antibodies, respectively. In the present work, we evaluated the contribution of lymphocytes in the regenerative process of crushed sciatic nerves of immunocompetent (wild-type, WT) and T and B-deficient (RAG-KO) mice. In knockout animals, we found increased amount of macrophages under basal conditions and during the initial phase of the regenerative process, that was evaluated at 2, 4 and 8 weeks after lesion (wal). That parallels with faster axonal regeneration evidenced by the quantification of neurofilament and a growth associated protein immunolabeling. The motor function, evaluated by the sciatic function index, was fully recovered in both mouse strains within 4 wal, either in a progressive fashion, as observed for RAG-KO mice, or presenting a subtle regression, as seen in WT mice between 2 and 3 wal. Interestingly, boosting the immune response by early adoptive transference of activated WT lymphocytes at 3 days after lesion improved motor recovery in WT and RAG-KO mice, which was not ameliorated when cells were transferred at 2 wal. When monitoring lymphocytes by in vivo imaging, in both mouse strains, cells migrated to the lesion site shortly after transference, remaining in the injured limb up to its complete motor recovery. Moreover, a first peak of hyperalgesia, determined by von-Frey test, was coincident with increased lymphocyte infiltration in the damaged paw. Overall, the present results suggest that a wave of immune cell infiltration takes place during subacute phase of axonal regeneration, resulting in transient set back of motor recovery following peripheral axonal injury. Moreover, modulation of the immune response can be an efficient approach to speed up nerve regeneration.